PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN TOMAT MENJADI DODOL DI DESA LENDANG NANGKA KECAMATAN MASBAGIK KABUPATEN LOMBOK TIMUR - Safira, Adinda; Lampiron, Muhamad; Hasbullah, Rakhan Qurani; Annisa Karini, Nudia; Azkia Tauchid, Mauli; Hilyatunnisa, Elok Sarah; Fakhrurrizal, Muhammad; Afra Alzena, Bunga; Elvira Damayanti, Queeny; Nurhasanah Jamalullail, Syarifah; Alamsyah, Ahmad (Jurnal Bakti Nusa, 2024)
The high rate of Indonesian people's appetite for snacks demands the production of snacks that comply with SNI, have good quality and are healthy. Tomatoes are one of the fruits that contain various nutrients and antioxidants that are needed by the body. Tomatoes can be processed into a variety of healthy and quality snack products including tomato dodol. The purpose of this community service activity is to improve community skills in processing dodol as a healthy snack made from tomatoes, while overcoming the problem of excessive tomato production in Lendang Nangka Village. The method used in this service is an action research approach combined with socialization of training in processing and packaging tomato dodol to the community in Lendang Nangka Village, Masbagik District, East Lombok Regency. The socialization and training of tomato dodol processing received enthusiasm and good attention from the women members of KWT and members of youth organizations.